(untitled) (Community Based Medical Journal, 2014)
The aim of this study to determine the prevalence of microalbuminuria as well as associated factors in non-diabetic hypertensive patients. Hospital-based cross sectional study. Main outcome of measure is microalbuminuria. A total of 100 nondiabetic hypertensive patients age 18 years without a history of pre-existing kidney disease attending the outpatient department of Community Based Medical College Bangladesh, Mymensingh over a period 6 months from June to December 2014 and who consented and met the criteria were enrolled in this study. A questionnaire including clinical and laboratory data was completed for all cases. The survey data were checked, coded and entered into a SPSS statistical package (Version 11.5). All variables were tested for normal distribution of the data. The data were then cleaned and analyzed using Chi-square (x2) Test, One-Way ANOVA statistics and Binary logistic regression model. Results were considered statistically significant for two-sided P values of <0.05. The overall prevalence of microalbuminuria was 17% of patients (11(64.7%) were male and 6(35.3%) female). The mean age and BMI were 49.2±9.1 years and 23.5±3.8 kg/m2 respectively. There were only 2(2%) patients whose systolic BP and diastolic BP were both well controlled (<140/˂90 mmHg), while normalization rates of either systolic BP (<140 mmHg) or diastolic BP (<90 mmHg) were 10% and 26% respectively. Age 50 years, low HDL, duration of HTN and triglyceride >150 mg/dl were found independent predictors of elevated UAE with ORs being 0.18, 3.9, 0.13 and 0.49 respectively. Microalbuminuria was not uncommon in non-diabetic hypertensive patients and older age, low HDL, high LDL, raised triglyceride and duration of HTN were significant predictors of microalbuminuria. There is an urgent need to screening of microalbuminuria should be mainstreamed into routine investigation and follow-up of patients with HBP. CBMJ 2014 July: Vol. 03 No. 02 P: 15-22